Late Triassic to Early Jurassic ecology: An insight into diet and trophic levels using non-traditional Ca isotopes - Davechand, Priyanka (University of the Witwatersrand, Johannesburg, 2023)
The diet and trophic structuring of organisms in deep time is poorly understood, making comparison of ancient and modern ecosystems challenging. Proxy data (e.g., dental morphology, jaw muscle reconstruction) remain the most common mode of palaeodietary inference, but the correlative strength of these proxies remains untested due to a lack of direct evidence and an incomplete sampling of palaeobiodiversity. These major challenges in palaeodietary reconstruction can be overcome using novel geochemical markers in fossilised tooth enamel, which provide direct evidence of palaeodiet and trophic relationships. Traditional stable isotopes of carbon, oxygen, and nitrogen have been used in the past to infer palaeodiets, but these elements are susceptible to diagenetic alteration during fossil preservation and require large sample amounts for assays. In contrast, non-traditional calcium (δ44/42Ca) isotopes are less susceptible to diagenesis and require significantly smaller sample amounts. This, together with the fractionation that Ca isotopes undergo as a bio-essential element, allows δ44/42Ca to be utilised on a broad range of palaeontological questions including assessing dietary range and trophic level. The diverse ecosystems of the Elliot Formation (Karoo Supergroup) in South Africa are represented by abundant fossils of a variety of reptilian and mammalian stem lineages that coexisted during the latest Triassic–earliest Jurassic interval (218–190 Ma). The broad range of body sizes, inferred dietary preferences, and phylogenetic positions make the Elliot palaeoecosystems an ideal natural laboratory in which to apply palaeodietary isotopic tools. This dissertation aims to assess the palaeotrophic divisions of the Elliot Formation vertebrates using non-traditional δ 44/42Ca isotopes. This research uses ion-exchange chromatography on vertebrate tooth enamel to assess the palaeodietary preferences of Elliot Formation reptilian and mammalian lineages. To obtain these data, existing techniques for sample preparation of non-traditional δ 44/42Ca isotopes were modified and optimised at the Wits Isotope Geoscience Laboratory (WIGL) at the University of the Witwatersrand. δ 44/42Ca analysis was conducted on a variety of specimens across a broad range of amniote lineages, ranging from: dinosaurs such as presumed herbivorous sauropodomorphs Massospondylus and Aardonyx, the presumed omnivorous ornithischian (Lesothosaurus and Heterodontosaurus), and the presumed carnivorous theropod Megapnosaurus; to cynodont therapsids (Tritylodon, Pachygenelus and Scalenodontoides); to pseudosuchians such as the crocodylomorphs Protosuchus and Orthosuchus and earlier branching taxa (‘rauisuchians’ and poposauroids). A leaching procedure was also tested to ensure that the results produced were not influenced by diagenetic biases. Once consistent and reproducible methods were finalised, column chemistry and Multicollector-Inductively Coupled Plasma Mass Spectrometery (MC-ICPMS) analysis was conducted on the different Karoo-aged specimens. There are various outcomes from this dissertation. One important outcome was the optimisation of time for Ca separation using ion-exchange chromatography. This allowed for a shorter chemical preparation time and increased the number of analyses completed per session. Another improvement of the method was that the leaching procedure can be used to control for any diagenetic biases by removing secondary calcite in samples as old as those from the Triassic–Jurassic period. Elliot taxa were then analysed, and significant differences were found between δ 44/42Ca values of large carnivorous pseudosuchians (‘rauisuchians’; -0.45 ‰ to -1.17 ‰) and co occurring herbivorous sauropodomorph genera (-0.26 ‰ to -0.69 ‰). These results indicated that non-traditional δ 44/42Ca isotopes can be used to understand trophic structures and palaeodiets in ecosystems at least 210 million years old. We also found that while some taxa had δ44/42Ca isotope values in-line with their presumed diets, other taxa had more diverse diets than initially presumed. δ 44/42Ca-enriched values in this study provide evidence for herbivory in crocodylomorph and the oldest theropod. There is also a possibility of an omnivorous diet for presumed herbivorous Lesothosaurus as the δ 44/42Ca values are relatively depleted to other herbivores. In addition to diet, calcium plays a major role in the formation of reptilian eggs and there are documented changes in δ 44/42Ca values during the reproductive cycle. To assess this in a living system, Crocodylus niloticus, was analysed to understand if δ 44/42Ca could be used to identify the difference in sex based on the δ 44/42Ca values. No isotopic differences were found between the juvenile male and female Crocodylus niloticus samples. Testing these important ecological principles in temporally constrained formations allows us to understand the historical nature of biodiversity changes, especially across periods when environments on Earth were experiencing extreme conditions. The ability to determine factors such as palaeodiet and palaeotrophic range will enable the development and improvement of palaeoecological analysis. This research presents the first ever δ 44/42Ca values on Karoo-aged vertebrate fossils and will have a large impact on how palaeoecological reconstruction is conducted in the future of palaeosciences.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Palaeodiet; Ca isotopes; Dinosaurs; Non-traditional isotopes; Tooth enamel; Palaeotrophic levels; UCTD; SDG-13: Climate action